Experiments for suitability of plastic heat exchangers for dehumidification applications. (25th July 2019) - Amer, Mohammed; Chen, Miao-Ru; Sajjad, Uzair; Ali, Hafiz Muhammad; Abbas, Naseem; Lu, Ming-Chang; Wang, Chi-Chuan
Highlights: Three novel plastic heat exchangers were introduced in this study. Condensation of humid air used in dehumidification heat exchanger was investigated. Bare tube plastic heat exchanger with asymmetry tube delivers further condensate. The asymmetry tube geometry design shows better heat transfer performance. Abstract: The present study conducted a series of experiments concerning the condensation of humid air used in a typical adsorption dehumidifier. The experiments were carried out with the standard ambient condition (27 °C dry bulb temperature and 21.2 °C wet bulb temperature) for the cold side. Yet the regeneration side (hot side) inlet temperature is 55 °C with RH% being 100%. Three novel plastic heat exchangers (plate plastic heat exchanger-PHX, bare tube plastic heat exchanger with asymmetry tube layout-BTHX, and round tube plastic heat exchanger with uniform tube layout-RTHX) were tested and compared experimentally. Test results, in terms of heat flux or heat transfer coefficient, show that the BTHX is superior to RTHX and PHX for offering additional condensate splashing mode. The splashing feature is especially beneficial for larger cold side flow rate since the plateau of heat transfer performance is moved toward larger cold side flow rate regime. The asymmetry tube geometry design (BTHX) shows even better heat transfer performance than the uniform tube bundle design (RTHX) for providing more space at the downstream of the tube bundle.